2015
DOI: 10.1177/1948550615595271
|View full text |Cite
|
Sign up to set email alerts
|

Maximizers, Satisficers, and Their Satisfaction With and Preferences for Reversible Versus Irreversible Decisions

Abstract: Previous research on decision reversibility has found that, although people believe they prefer reversible decisions, irreversible decisions yield the most satisfaction. Two studies investigated whether these findings are moderated by individuals' tendencies toward maximizing (decision making via extensive search for the best option) versus satisficing (decision making via less exhaustive search and less optimizing). Study 1 found that satisficers were more satisfied following an irreversible decision about a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 24 publications
0
24
1
1
Order By: Relevance
“…First, they contribute to the growing literature examining moderators of maximizers' satisfaction with their choices, such as reversible versus irreversible choices (Shiner 2015) or maximization goals versus strategy (Hughes and Scholer 2017). Second, they converge with recent studies showing that maximizers' choice satisfaction is undermined by a high responsiveness to normative concerns, such as choosing the objectively best option (Luan and Li 2017a), and external influences, such as comparing one's choices with others' choices (Weaver et al 2015).…”
Section: Theoretical and Practical Contributionsmentioning
confidence: 55%
“…First, they contribute to the growing literature examining moderators of maximizers' satisfaction with their choices, such as reversible versus irreversible choices (Shiner 2015) or maximization goals versus strategy (Hughes and Scholer 2017). Second, they converge with recent studies showing that maximizers' choice satisfaction is undermined by a high responsiveness to normative concerns, such as choosing the objectively best option (Luan and Li 2017a), and external influences, such as comparing one's choices with others' choices (Weaver et al 2015).…”
Section: Theoretical and Practical Contributionsmentioning
confidence: 55%
“…This phenomenon is called "maximization paradox". Researchers have found this phenomenon in all kinds of fields such as job search (Iyengar et al, 2006), romance (Mikkelson & Pauley 2013), and consumption (Weaver et al, 2015;Shiner, 2016 …”
Section: The Psychological Roots Of Maximization Paradoxmentioning
confidence: 97%
“…They are usually more relevant to perfectionism and are less open (Bruine de Bruin, . They are more competitive (Weaver et al, 2015); the latter includes decision visibility (Lin, 2015), decision-making context reversibility (Shiner, 2016), socio-cultural environment, and socio-economic level (Roets, Schwartz, & Guan, 2012;Oishi, Tsutsui, Eggleston, & Galinha, 2014) which all have an impact on ones' decision-making style and their experiences. Datu (2015) found that in the cultural context of collectivism, maximizing tendency can make people with positive emotions more aware of the meaning of life.…”
Section: Explore the Factors That Influence Maximizer's Decision-makimentioning
confidence: 99%
“…Sedangkan pada masyarakat Jepang, ditemukan bahwa maximizer lebih depresi, kurang bahagia, dan kurang puas dengan kehidupannya, baik ketika menggunakan skala MS maupun MTS. Sejumlah penelitian menunjukkan bahwa maximizer akan lebih puas dengan keputusannya ketika pilihan tersebut berkebalikan atau berbeda dengan pilihan awal, oleh karena itu (Shiner, 2015) menegaskan bahwa jika seorang maximizer diberikan alternatif pilihan yang jelas akan cenderung lebih puas dengan keputusannya.…”
Section: Hasil Dan Pembahasanunclassified